Cordyceps spp.: A Review on Its Immune-Stimulatory and Other Biological Potentials - Das, Gitishree; Shin, Han-Seung; Leyva-Gómez, Gerardo; Prado-Audelo, María L. Del; Cortes, Hernán; Singh, Yengkhom Disco; Panda, Manasa Kumar; Mishra, Abhay Prakash; Nigam, Manisha; Saklani, Sarla; Chaturi, Praveen Kumar; Martorell, Miquel; et al. (Frontiers in Pharmacology, 2021)
In recent decades, interest in the Cordyceps genus has amplified due to its immunostimulatory potential. Cordyceps species, its extracts, and bioactive constituents have been related with cytokine production such as interleukin (IL)-1β, IL-2, IL-6, IL-8, IL-10, IL-12, and tumor necrosis factor (TNF)-α, phagocytosis stimulation of immune cells, nitric oxide production by increasing inducible nitric oxide synthase (iNOS) activity, and stimulation of inflammatory response via mitogen-activated protein kinase (MAPK) pathway. Other pharmacological activities like antioxidant, anti-cancer, antihyperlipidemic, anti-diabetic, anti-fatigue, anti-aging, hypocholesterolemic, hypotensive, vasorelaxation, anti-depressant, aphrodisiac, and kidney protection, has been reported in pre-clinical studies. These biological activities are correlated with the bioactive compounds present in Cordyceps including nucleosides, sterols, flavonoids, cyclic peptides, phenolic, bioxanthracenes, polyketides, and alkaloids, being the cyclic peptides compounds the most studied. An organized review of the existing literature was executed by surveying several databanks like PubMed, Scopus, etc. using keywords like Cordyceps, cordycepin, immune system, immunostimulation, immunomodulatory, pharmacology, anti-cancer, anti-viral, clinical trials, ethnomedicine, pharmacology, phytochemical analysis, and different species names. This review collects and analyzes state-of-the-art about the properties of Cordyceps species along with ethnopharmacological properties, application in food, chemical compounds, extraction of bioactive compounds, and various pharmacological properties with a special focus on the stimulatory properties of immunity.